Pendampingan Guru SD dalam Mendesain dan Memanfaatkan E-book Interaktif Untuk Meningkatkan Inovasi Pembelajaran Matematika: Pengabdian - Muhammad Nurwahidin; Riswandi; Maya Adina Pratama; Dina Apryani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to enhance the understanding and skills of elementary school teachers in designing and implementing interactive e-books based on real-life situations as innovative mathematics learning media relevant to everyday life contexts. The program was conducted at SD Negeri 2 Wonodadi, Pringsewu Regency, involving nine active classroom teachers as participants. The implementation methods included needs analysis, technical training on e-book creation, assistance in production and classroom implementation, and evaluation of activities through a participatory and reflective approach. Each stage is designed based on hands-on practice (learning by doing) to ensure active participant engagement. The activity results showed a significant increase in teachers' pedagogical competence and digital literacy, with an average understanding score improvement of 28 points between the pre-test and post-test. Almost all participants successfully designed interactive e-book products that met the content, visual, and interactivity criteria. In addition to producing digital learning products, this activity also formed the “Wonodadi Digital Teachers” community as a manifestation of the sustainability of technology-based learning innovation in elementary schools.